Kompleksitas Kalimat Bahasa Indonesia Siswa Kelas IV—VI Sekolah Dasar - Berlian Pancarrani; Abd. Syukur Ghazali; Nurchasanah Nurchasanah (Graduate School of Universitas Negeri Malang, 2018)
Abstract: This study aims to describe the complexity of sentences based on the structure and its elements. This research uses qualitative approach and cross sectional design. Data in this research is in the form of Indonesian sentence from students’ essay seen from element and its structure. The data of this research is written by students of grade IV, V, and VI SDN Kampungdalem 1 and SDN Suwaluh 1. The result of this study shows (1) based on the structure, students have been able to arrange seven basic sentence patterns and compose three varieties of transformation sentences, and (2) based on its elements, students have used different types of word classes including nouns, verbs, adjectives, and pronouns.Abstrak: Penelitian ini bertujuan untuk mendeskripsikan kompleksitas kalimat berdasarkan struktur dan unsurnya. Penelitian ini menggunakan pendekatan kualitatif dan dengan rancangan cross sectional. Data dalam penelitian ini berupa kalimat bahasa Indonesia dalam karangan siswa dilihat dari unsur dan strukturnya. Sumber data penelitian ini adalah karangan yang ditulis siswa kelas IV, V, dan VI SDN Kampungdalem 1 dan SDN Suwaluh 1. Hasil dari penelitian ini menunjukkan (1) berdasarkan strukturnya siswa telah mampu menyusun tujuh pola kalimat dasar dan menyusun tiga ragam kalimat tranformasi, dan (2) berdasarkan unsurnya siswa telah menggunakan beragam jenis kelas kata, meliputi nomina, verba, ajektiva, dan pronomina.